2010
DOI: 10.4067/s0716-97602010000100002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of two immunohistochemical methods for antigen retrieval in the optical lobe of the honeybee Apis mellifera: Myosin-v assay

Abstract: The present study compared two heating methods currently used for antigen retrieval (AR) immunostaining: the microwave oven and the steam cooker. Myosin-V, a molecular motor involved in vesicle transport, was used as a neuronal marker in honeybee Apis mellifera brains fixed in formalin. Overall, the steam cooker showed the most satisfactory AR results. At 100 o C, tissue morphology was maintained and revealed epitope recovery, while evaporation of the AR solution was markedly reduced; this is important for sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Cristina et al 8 found that antigen retrieval by high-pressure cooking demonstrated a specificity of 100% in the diagnosis of κ-type or λ-type non-Hodgkin's lymphoma. In detection of myosin-V by immunohistochemistry (IHC) using formalin-fixed brain tissue from bees, Calabrin et al 9 found that antigen retrieval by high-pressure steam cooking gave satisfactory results.…”
Section: Introductionmentioning
confidence: 99%
“…Cristina et al 8 found that antigen retrieval by high-pressure cooking demonstrated a specificity of 100% in the diagnosis of κ-type or λ-type non-Hodgkin's lymphoma. In detection of myosin-V by immunohistochemistry (IHC) using formalin-fixed brain tissue from bees, Calabrin et al 9 found that antigen retrieval by high-pressure steam cooking gave satisfactory results.…”
Section: Introductionmentioning
confidence: 99%